A Case of Congenital Dacryocystocele - Ha, You Jin (Korean Dermatological Association; The Korean Society for Investigative Dermatology, 2010)
A 6-day-old infant presented with a deeply bluish cystic mass below the right medial canthus. She had been born healthy. Under the impression of a hemangioma brain computed tomography was conducted. As a result, a diagnosis of congenital dacryocystocele was made. We present this case to show that it is important for a dermatologist to correctly identify congenital dacryocystoceles and appropriately refer the infant to a pediatric ophthalmologist prior to performing invasive measures.